Failure analysis of boron/glass hybrid composite laminates with various cutouts shapes and sizes under biaxial tension / Muhammad Amir Azhan Zulkifli - Zulkifli, Muhammad Amir Azhan (2022)
Hybrid composite laminates have recently increasing attention in precision engineering field such as aerospace and automotive industries. Studies for failure behaviour of hybrid laminated composites under uniform biaxial loads have been obtained without considering cutouts. Nevertheless, in practice, the structures are provided with cutouts of various sizes subjected to biaxial tension. This study intends to analyse the failure behaviour of Boron/Glass hybrid composite laminates material with various cutout shapes and sizes under biaxial tension. Initially, failure analysis was performed for laminated composite plate without cutout with lamination sequence of (Ɵ4/04/-Ɵ4)s where the angle, 9 ranges from 0° to 90° using a Finite Element Analysis (FEA) software, ANSYS. The accuracy of the analysis were compared using analytical method using Matlab based on First Order Shear Deformation Theory (FSDT). Then, next stage involved the failure analysis of hybrid laminated composite plate with various cutouts (circle, diamond and square) and sizes. The ply angles of (0/±45/90)s, (0/±45)s and (0/90)s are modelled. These analyses were performed to determine the failure load by employing Maximum stress criterion and Tsai-Wu criterion. The failure curves were plotted and analysed. Results of Matlab code and FEA based ANSYS software, are in close agreement.